2008
DOI: 10.1175/2008waf2222136.1
|View full text |Cite
|
Sign up to set email alerts
|

The Initiation and Evolution of Multiple Modes of Convection within a Meso-Alpha-Scale Region

Abstract: On 30 March 2006, a convective episode occurred featuring isolated supercells, a mesoscale convective system (MCS) with parallel stratiform (PS) precipitation, and an MCS with leading stratiform (LS) precipitation. These three distinct convective modes occurred simultaneously across the same region in eastern Kansas. To better understand the mechanisms that govern such events, this study examined the 30 March 2006 episode through a combination of an observation-based case study and numerical simulations. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
(56 reference statements)
3
12
0
Order By: Relevance
“…The authors believe that quantities such as the strength of the capping inversion and the nature of the atmospheric moisture profiles do play a role in how storms evolve. For example, modeling work by French and Parker (2008) indicated that temperature perturbations within convective outflows were sensitive to changes in vertical moisture profiles. These perturbations, in addition to the amount of convective inhibition, can determine how effectively the outflows can generate new convection, which, in turn, would have an influence on future storm evolution.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The authors believe that quantities such as the strength of the capping inversion and the nature of the atmospheric moisture profiles do play a role in how storms evolve. For example, modeling work by French and Parker (2008) indicated that temperature perturbations within convective outflows were sensitive to changes in vertical moisture profiles. These perturbations, in addition to the amount of convective inhibition, can determine how effectively the outflows can generate new convection, which, in turn, would have an influence on future storm evolution.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…2) or similarly in the buoyancy-shear domain (see Stensrud et al 1997), however, these methods are not sufficient to unambiguously distinguish between modes. Similarly, French and Parker (2008) show that environmental variations in thermodynamic and wind shear profiles within a confined area were responsible for a multimode convective day in that region. Markowski et al (1998), for example, document that SREH is highly variable on small spatial and temporal scales.…”
Section: Importance Of Convective Morphologymentioning
confidence: 99%
“…Generally speaking, significant tornadoes and large hail often occur with supercell thunderstorms (e.g., Doswell and Burgess 1993;Davies-Jones et al 2001) whereas widespread damaging straight-line winds are more frequently produced by linear modes, particularly bow echoes (e.g., Fujita 1978;Przybylinski 1995). This becomes complicated, however, in cases where multiple organizational modes are present within a localized area (e.g., French and Parker 2008), especially when these modes merge into a single system. This can help them anticipate which severe weather hazards may occur and how those hazards may change with time.…”
Section: Introductionmentioning
confidence: 99%